Nanopore Data-Driven Chromosome-Level Assembly of Flax Genome - Alexander A. Arkhipov; Elena N. Pushkova; Nadezhda L. Bolsheva; Tatiana A. Rozhmina; Elena V. Borkhert; Daiana A. Zhernova; Tatiana Yu. Rybakova; Nikolai M. Barsukov; Olesya D. Moskalenko; Elizaveta A. Sigova; Ekaterina M. Dvorianinova; Nataliya V. Melnikova; et al. (Plants)
Flax is an important crop grown for seed and fiber. Flax chromosome number is 2n = 30, and its genome size is about 450–480 Mb. To date, the genomes of several flax varieties have been sequenced and assembled. However, the obtained assemblies are still far from the telomere-to-telomere (T2T) level. We sequenced the genome of flax variety K-3018 on the Oxford Nanopore Technologies (ONT) platform and obtained 57.7 Gb of R10 simplex reads with an N50 = 18.4 kb (~120× genome coverage). ONT reads longer than 50 kb were kept as ultra-long ones (~10× genome coverage), and the rest of the ONT reads were corrected using the HERRO R10 model (quality > Q10, length > 10 kb, ~60× genome coverage remained). The genome was assembled using Hifiasm and Verkko. The Hifiasm-generated assembly was 489.1 Mb in length with 54 contigs and an N50 = 28.1 Mb. Verkko produced a very similar but more fragmented genome: 489.1 Mb, 134 contigs, N50 = 17.4 Mb. In the assembly by Hifiasm, eight chromosomes consisted of a single contig with telomeric repeats at both ends. In addition, five chromosomes comprised two contigs and two chromosomes comprised three contigs. These chromosomes also had telomeric repeats at their ends. The Hifiasm-generated assembly of variety K-3018 had similar contiguity but was likely more complete and accurate than the main fifteen-chromosome assembly of variety YY5 (produced from PacBio data and scaffolded with Hi-C data), the most contiguous flax genome assembly at the time of this writing. We suggest that sufficient genome coverage with long ONT R10 simplex reads is a viable alternative to PacBio plus Hi-C data for a high-precision T2T genome assembly of flax, opening new perspectives for whole-genome studies of flax.